Methodological assumptions influence on environmental risk management scientific research conduction - Merlin, Fabrício Kurman; Loureiro, Solange Maria; Pereira, Vera Lúcia Duarte do Valle (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This article aims to discuss the need for proper understanding and mastery on the part of the researchers on the dominant philosophical underpinnings, logics of rationality (methods) and characterizations used in conducting scientific research, and the importance in considering the complementarity between these underpinnings, on the approach of the phenomena, for the construction of scientific knowledge. For such, it presents the analysis of a set of selected papers in the environmental risk management area, using the reference of Pacheco Junior, Pereira and Pereira Filho (2007), on the disclosure of the influence of methodological assumptions in the development of scientific research.